Celecoxib Protects Hyperoxia-Induced Lung Injury via NF-κB and AQP1 - Liu, Dongyun; Wang, Yuguang; Li, Lili; Zhao, Han; Li, Liangliang; Liu, Yan; Jiang, Hong; Li, Xianghong; Zhang, Rui (Frontiers in Pediatrics, 2019)
Objective: There is an increasing incidence of bronchopulmonary dysplasia (BDP) in preterm infants in China, which is the key issue affecting their survival rate and life quality. This study was performed to better understand the mechanism of protective effect of celecoxib on hyperoxia induced injury. Methods: Hyperoxia BPD model was established using newborn Sprague-Dawley (SD) rats exposed to high O2 level (85%). Celecoxib treatment was also conducted. Histology of lung tissue samples were analyzed. Functional studies were systematically performed using the lung tissues and A549 cells. Results: Hyperoxia disrupted lung development in SD rats. Celecoxib alleviated the damaged lung development. NF-κB and Aquaporin (AQP) 1 were identified as the pathways in the hyperoxia-induced lung injury. We have shown that hyperoxia activated NF-κB pathway through increased nucleus translocation and repressed AQP1 expression. On the contrary, celecoxib inhibited NF-κB phosphorylation and nucleus translocation and increased AQP1 expression through inhibiting COX2 activity. Additionally, celecoxib also rescued apoptosis induced by hyperoxia. Conclusion: Our study identified NF-κB and AQP1 as the pathways in the hyperoxia-induced lung injury in the hyperoxia BPD model SD rats and it provided a better understanding of the protective effect of celecoxib. It suggests NF-κB and AQP1 may be as potential targets for treating newborns with BPD.